Subtilisin-like proteases in plant–pathogen recognition and immune priming: a perspective - Figueiredo, Andreia; Monteiro, Filipa; Sebastiana, Mónica (Frontiers in Plant Science, 2014)
Subtilisin-like proteases (subtilases) are serine proteases that fulfil highly specific functions in plant development and signaling cascades. Over the last decades, it has been shown that several subtilases are specifically induced following pathogen infection and very recently an Arabidopsis subtilase (SBT3.3) was hypothesised to function as a receptor located in the plasma membrane activating downstream immune signaling processes. Despite their prevalence and potential relevance in the regulation of plant defense mechanisms and crop improvement, our current understanding of subtilase function is still very limited. In this perspective article, we overview the current status and highlight the involvement of subtilases in pathogen recognition and immune priming.